Implementation of Contextual-Based Educational Games To Develop Students' Character and Conceptual Understanding on Legal Norms Material in Grade V of UPTD SD Negeri 5 Makmur - Annisa, Dian; Khairani, Cut; Muharramsyah , Rambang (FKIP - Universitas Riau, 2025)
This study aims to analyze the implementation of contextual-based educational games in developing students' character and conceptual understanding of legal norms material in grade V at UPTD SD Negeri 5 Makmur. The research employed a descriptive qualitative approach with data collection techniques through in-depth interviews, observations, and documentation. Research subjects included grade V teachers, school principals, colleagues, and 5 representative students from 33 grade V students. Data analysis used the Miles and Huberman model strengthened by NVivo 15 coding software. The results showed: (1) Implementation of educational games proceeded very well (91.5%) through systematic planning, implementation, and evaluation stages; (2) Students' discipline and responsibility character developed significantly from external to internal discipline; (3) Students' conceptual understanding improved in identifying, explaining, and applying legal norms although still limited to simple cases; (4) Student and teacher responses were very positive with high enthusiasm (96.8%) and active involvement. This research confirms the effectiveness of contextual-based educational games as learning innovation that integrates cognitive, affective, and psychomotor aspects in learning legal norms at elementary school.